Penglipuran Village Festival IX 2022: A Cultural Festival at The Cleanest Village in The World - Ida Bagus Agung Wicaksana (Bali Tourism Journal, 2022)
The Vice Regent of Bangli, I Wayan Diar, officially closed The Penglipuran Village Festival IX 2022 on Wednesday evening, 14 December 2022. The closing ceremony of the six days festival was centered at the Penglipuran Village Hall, Bangli. The head of the Bangli Sub-District, the Bangli Regency Tourism and Culture Officer, the Bangli Regency Education and Youth Agency officer, the competition winners, and the local community attended the event. The Penglipuran Village Festival IX 2022 was an event in Penglipuran Tourism Village, Kubu Subdistrict, Bangli Regency. It was a village festival encompassing various activities and competitions, such as cultural parades, exhibitions, Balinese dance competitions, performing arts, talk shows, Megibung, yoga, and other mass activities. Penglipuran residents strongly hold their ancestor’s values to preserve their customs and philosophy of living. For instance, the folk conserves the old bamboo forest north of their village, maintaining the traditional architecture. Penglipuran Village has become one of Indonesia's pioneers of successful tourism villages, even internationally recognized by various tourism organizations. In early 2016, Penglipuran Village in Bali, Giethoorn Villages in the Netherlands, and Mawlynnong Village in India have named the cleanest villages in the world. The successful Penglipuran Village Festival IX was expected to be a trajectory point for tourism recovery after the Covid-19 pandemic. Especially as an epicenter for tourism promotion in Bali and Bangli particularly. With the theme of Resurrecting the spirit of environmental conservation, the organizer looked forward to raising the morale of ecological preservation.